Hit refresh the quest to rediscover microsoft's soul and imagine a better future for everyone - Nadella, Satya (Harper Audio, 2017)
The New York Times bestseller Hit Refresh is about individual change, about the transformation happening inside of Microsoft and the technology that will soon impact all of our lives?the arrival of the most exciting and disruptive wave of technology humankind has experienced: artificial intelligence, mixed reality, and quantum computing. It?s about how people, organizations, and societies can and must transform and ?hit refresh? in their persistent quest for new energy, new ideas, and continued relevance and renewal.
Keywords: Microsoft